FORMULATION AND EVALUATION OF PHYTOSOME LOTION FROM NOTHOPANAX SCUTELLARIUM LEAF EXTRACT FOR HAIR GROWTH - RAHMI, IKA AULIA; MUN’IM, ABDUL; JUFRI, MAHDI (International Journal of Applied Pharmaceutics, 2021)
Objective: The purpose of this study was to formulate a phytosome lotion from Mangkokan leaf using green solvent extraction. Methods: Ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate, combined with microwave-assisted extraction, was used to obtain flavonoid compounds. Mangkokan leaf extract was formulated into a phytosome with three different ratios of phospholipon (1:0.5), (1:1), and (1:2). Three phytosome formulas were analyzed to identify the best formula. The analysis included morphology, particle size, and zeta potential, entrapment efficiency, and spectrum analysis using an FTIR spectrophotometer. The formula which chosen was formulated into three lotion formulas with different concentration (20%; 25%; 30%) then, evaluated for physical stability, and hair growth activity test included hair length, weight, and diameter. Minoxidil and non-phytosome lotion were used as comparison. Data were analyzed using two-way ANOVA. Results: The FTIR of phytosome was confirmed a complex formation of extract and phospholipon. The phytosome morphology was displayed irregular spherical vesicles. Phytosome with the ratio of phospholipon (1:0.5) was formulated into lotion because has a smaller particle size (289 nm), and higher entrapment efficiency (99.76%±0.24) than others. Phytosome lotions displayed higher activity than 2% minoxidil (p = 0.0001). Phytosome lotion (30%) thus showed the highest efficacy for hair length, weight and diameter. Conclusion: Mangkokan leaf that extracted using 1-butyl-3-methylimidazolium tetrafluoroborate solvent combined with microwave-assisted extraction then formulated into phytosome lotion has higher activity than 2% minoxidil. Lotion that contains 30% mangkokan leaf phytosome was showed the highest efficacy.